INTERNATIONAL AND DOMESTIC PRACTICES OF ASSISTANT TEACHER'S WORK - Sytniakivska , Svitlana; Illina, Olha (Physical and Mathematical Education, 2022)
Formulation of the problem. It is stated that in Ukraine inclusive education is provided by an inclusive school - an educational institution where a physical environment is created as well as curricula and plans are implemented, teaching methods and forms are used, resources and specialists are involved to provide educational services according to every child's needs. Accordingly, there is a problem of defining and specifying the functions and responsibilities of professionals being at work in such an institution.Materials and methods. Methods of theoretical analysis and comparison are applied. Approaches to involving a teacher's assistant in the process of providing support to children with special educational needs in foreign countries are analyzed. The experience of teacher's assistant work in inclusive educational institutions of Ukraine is also described.Results. It is noted that the level of social inclusion is an indicator of the civilization of society, a criterion of its democracy and humanistic orientation. The introduction of inclusive education guarantees the realization of the right to study at the place of residence, which provides an opportunity to be integrated into society on a common basis, to have support from family, friends, small social groups in which the primary socialization of the individual occurs. Thus, inclusive education is one of the main ways of social inclusion. It is determined that the policy of different countries in the field of inclusive education is determined by the social problems that dominate in a particular country in a given period. It was found that the tasks and functions of a teacher's assistant in different countries differ and depend on the specific problems that arise in the process of inclusive education of children with special educational needs. The work of a teacher's assistant in foreign countries is not limited to supporting children with disabilities in the educational process, but can also be aimed at supporting children from different ethnic and linguistic communities, children of refugees and migrants, etc. The basic principles of professional activity of such specialists in Ukraine are also described.Conclusions. The conclusion is made about the need to improve the system of assistance within the inclusive education in Ukraine. This system must be flexible and dynamic and adapt to the real needs of the pupil and the demands of the teacher. The use of foreign experience in defining the job responsibilities of a teacher's assistant in every individual case, the distribution of roles will increase the effectiveness of the process of inclusive education of children with special educational needs.
Keywords: inclusion; inclusive education; a child with special educational needs; a child with disabilities; teacher's assistant; pupil's assistant; child's assistant